Social Primitivism and Classicism: Programmatic Construct and its - Tichy, Martin (Bohemica Olomucensia, 2025)
The manifesto published by Literarni skupina (Literary Group) in 1922 attempted to synthesize and reinterpret numerous concepts appearing in the critical discourse of the early 1920s; among them, classicism and primitivism represented the desire for a new form of social poetry. These two directives were present in the young criticism as lessons of simplification and a sense of reality, as evidenced by the texts of Karel Teige and other critics in the circle of Devetsil. As a part of discussion with Devetsil on new/proletarian art, Frantisek Gotz and Literarni skupina promulgated the synthesis of classicism and primitivism in the manifesto. But subsequent texts of Gotz and others demonstrated that this synthesis was only chimerical: there was no programmatic aim to revive the tradition (and classicism had no basis outside of it), while primitivism was the vivid reality of poetic writing.
Keywords: classicism; primitivism; proletarian art; avant-garde